2015
DOI: 10.1111/jvh.12418
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated interferon alfa for chronic hepatitis B: systematic review and meta‐analysis

Abstract: SUMMARY. Conventional interferon alfa and nucleos(t)ide analogues, such as lamivudine, are frequently used for chronic hepatitis B (CHB) treatment, but are associated with adverse effects and viral resistance. Here we performed a systematic review and meta-analysis evaluating all studies of pegylated interferon alfa (PEG-IFNa) treatment in hepatitis B e antigen (HBeAg)-positive and HBeAg-negative patients with CHB. We searched electronic databases -PubMed, EMBASE, Cochrane Library and LILACS -for randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
1
20
1
2
Order By: Relevance
“…However, the therapeutic outcome of Peg‐IFNα on CHB patients is still suboptimal. Previous studies reported that sustained virological response rates (HBV DNA <2,000 IU/mL) were only 30% in hepatitis B e antigen (HBeAg)‐positive and 43% in HBeAg‐negative patients at 24 weeks after completion of a 48‐week Peg‐IFNα treatment . Improving the response to IFNα‐based treatment remains an essential issue in the management of CHB patients.…”
mentioning
confidence: 99%
“…However, the therapeutic outcome of Peg‐IFNα on CHB patients is still suboptimal. Previous studies reported that sustained virological response rates (HBV DNA <2,000 IU/mL) were only 30% in hepatitis B e antigen (HBeAg)‐positive and 43% in HBeAg‐negative patients at 24 weeks after completion of a 48‐week Peg‐IFNα treatment . Improving the response to IFNα‐based treatment remains an essential issue in the management of CHB patients.…”
mentioning
confidence: 99%
“…13 Combining PegIFN with a potent NA has shown a favourable impact on HBeAg seroclearance and HBsAg seroclearance. 14,15 While more recent clinical trials in HBeAg-positive patients have concluded that adding or switching to PegIFN from an already existing potent NA-based regimen could increase rates of HBeAg seroclearance and HBeAg seroconversion, even after completing PegIFN. 16,17 Despite these encouraging data, it remains unknown whether such a treatment strategy would be beneficial to HIV-HBV co-infected patients, for whom interferon-based treatments are generally less successful.…”
Section: Chronic Hepatitis B Virus (Hbv) Infection Is Observed In Roumentioning
confidence: 99%
“…In HBV mono‐infection, treatment with pegylated interferon (PegIFN) has demonstrated higher rates of HBeAg seroconversion compared to nucleoside/nucleotide analogues (NA) with lower antiviral potency . Combining PegIFN with a potent NA has shown a favourable impact on HBeAg seroclearance and HBsAg seroclearance . While more recent clinical trials in HBeAg‐positive patients have concluded that adding or switching to PegIFN from an already existing potent NA‐based regimen could increase rates of HBeAg seroclearance and HBeAg seroconversion, even after completing PegIFN .…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, sete agentes terapêuticos encontram-se aprovados para uso na hepatite B crônica na maioria dos países do mundo: adefovir, entecavir, lamivudina, telbivudina, tenofovir, interferon-alfa e interferon peguilado (52)(53)(54)(55)(56)(57)(58)(59) . A tabela 2 mostra os principais análogos de nucleos(t)ídeos aprovados.…”
Section: Arsenal Terapêuticounclassified
“…A descontinuação do tratamento antiviral geralmente leva à perda de controle viral e desenvolvimento de variantes de resistência antiviral (52,96,97) .…”
Section: A Adesão Ao Tratamento Na Hepatite B Crônicaunclassified